2016
DOI: 10.4172/1747-0862.1000198
|View full text |Cite
|
Sign up to set email alerts
|

Use of Blood as a Surrogate Model for the Assessment of Visceral Adipose Tissue Methylation Profiles Associated with the Metabolic Syndrome in Men

Abstract: Epigenetic mechanisms are known to be involved in tissue-specific differentiation. DNA methylation patterns have been shown to be largely conserved across tissues but with variation for specific genes. However, it is unclear whether the variability observed in the methylation profile of a metabolically active tissue is reflected in other sources such as hematopoietic tissue. This study aimed to test blood genome-wide CpG site methylation levels as a surrogate model for visceral adipose tissue (VAT) methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
(70 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, DNA methylation levels are specific to the type of cell and tissue (Bell et al, 2012). These methylation profiles in cord blood leukocytes might not represent DNA methylation in other tissues even though patterns are globally conserved (Ma et al, 2014; Ronn et al, 2015; Guénard et al, 2016). Finally, annotation of genetic variants has been deemed as inconsistent across databases, incomplete, and subjective toward known genes and pathway analysis that is statistically unpowered (Aslibekyan et al, 2014b).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, DNA methylation levels are specific to the type of cell and tissue (Bell et al, 2012). These methylation profiles in cord blood leukocytes might not represent DNA methylation in other tissues even though patterns are globally conserved (Ma et al, 2014; Ronn et al, 2015; Guénard et al, 2016). Finally, annotation of genetic variants has been deemed as inconsistent across databases, incomplete, and subjective toward known genes and pathway analysis that is statistically unpowered (Aslibekyan et al, 2014b).…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have also suggested that whole genome differential methylation patterns derived from blood leukocytes (BL) may be used as surrogates of those derived from VAT. More specifically, a set of differentially methylated cytosine-phosphate-guanine (CpG) sites, common in VAT and BL, were shown to successfully discriminate men with or without metabolic syndrome [ 100 ]. These and other results suggest that BL methylation levels could be a good marker of VAT DNA methylation [ 101 ], and could then be used to determine the effect of a nutritional intervention on the epigenetic profile, and therefore on metabolic health related to VAT accumulation.…”
Section: Deep Phenotypingmentioning
confidence: 99%
“…Focusing on epigenetics, we and others have shown that altered DNA methylation in obesity would be associated to increased prevalence of metabolic comorbidities [813]. As such, both global methylation differences observed in blood and tissue-specific methylation alterations have been found to be associated with healthy or unhealthy obesity phenotypes [14, 15]. Likewise, given the innate plasticity of DNA methylation at cytosine-phosphate-guanine (CpG) dinucleotides [16], its modulation appears to be mediated through numerous environmental and lifestyle factors, such as diet or metabolic stress, as well as by intrinsic individual features, mainly sex and age [17].…”
Section: Introductionmentioning
confidence: 99%